Особиста бібліотека Омеляна Пріцака в Національному університеті "Києво-Могилянська академія" як джерело дослідження наукової біографії вченого - Сидорчук, Т. (Краєзнавство, 2019)
В статті аналізується особиста бібліотечна колекція видатного вченого ХХ століття в галузі гуманітаристики, організатора світової та української науки Омеляна Пріцака (1919-2006), а також висвітлюється її потенціал для реконструкції інтелектуальної біографії власника. Розкриваються обставини передачі бібліотеки до Національного університету «Києво-Могилянська академія» у 2007 році та принципи її облаштування і функціонування у структурі наукової бібліотеки університету. Простежується процес формування бібліотеки вченим протягом понад 70 років, від часу навчання у Львівському університеті у 1930-х роках і до його смерті у 2006 році у Бостоні, Массачусетс, США. Визначені етапи трансформації бібліотеки О.Пріцака-студента – від декількох десятків книг, які він вивіз із собою з України в 1943 році для навчання у Берлінському університеті, до бібліотеки О. Пріцака-вченого, яка стала його справжнім дослідницьким інструментарієм та лабораторією. Аналізуються хронологічні межі, кількісні параметри та змістовне наповнення кожної складової бібліотеки – друковані видання і періодика та рукописні матеріали і документи. Проаналізовано відображення в книжковій та архівній колекціях всіх періодів наукової біографії вченого, його різноманітні дослідницькі зацікавлення, участь у міжнародних академічних інституціях та форумах, створення ним наукових установ, а також багатолітні контакти з видатними науковцями, державними, церковними та культурними діячами багатьох країн світу. The Outline of the Problem. The contribution of Omeljan Pritsak into the global and Ukrainian science, as well as manuscripts and printed historical and cultural materials, collected by him, provides a real basis and groundwork for determination of his private library as historical and spiritual heritage of Ukrainian and global science and culture. Methods of Research. The complexity of undertaking a holistic and multifaceted study of Omeljan Pritsak’s intellectual concept in relation to gathering of his own research library requires to disclose the methodological aspect of the problem and to make a retrospective journey into the historical context in which most of the books, collected by the scholar, were found. Accordingly, the main methods, used by the author, were the method of synthetic analysis, from the one side, and method of retrospection, from the another side. Survey of the Results. The private library of prominent scholar of the twentieth century in the field of Humanities, the organizer of the global and Ukrainian science Omeljan Pritsak (1919-2006) is analyzed in the article and also the reconstruction of intellectual biography of its owner is reconstructed. The peculiarities of transferring of the library to National University «Kyiv-Mohyla Academy» in 2007 are revealed as well as the principles of its structuring and functioning in general structure of the scientific library of University. The process of formation of the library by the scholar in the time span of seventy years from the educational period in L’viv’s University in 1930s up to his death in 2006 in Boston, Massachusetts, USA is well seeing. The stages of transformation of the library of Pritsak as a student – from some dozens of books, which he took from Ukraine in 1943 for the purposes of education in Berlin’s University up to the library of Pritsak – scholar, which became his real tool for the research and creative laboratory, are determined. The chronological periods, the quantitate parameters and content feeling of the each part of library – the publishing editions, periodicals, manuscripts and documents is analyzed. The reflection in the framework of library and archival collection of all the periods of intellectual biography of scholar, his various research interests, the participation in international academic institutions and forums, the creation by him the research organizations, as well as his long term contacts with outstanding scholars, statesmen, clericals, artists from many countries all around the world is analyzed. Conclusions.The personal library of Omeljan Pritsak is consisted from two interrelated collections: printed books and periodicals; archive. Printed editions more than seventeen thousand volumes are numbered and unique incunabulum from the sixteenth – seventeenth centuries as well as rare and valuable books from the nineteenth – twentieth, translated into the hundred languages are included. Archive contains 42 hand scripted books from the sixteenth – nineteenth centuries, personal documents, the materials, illustrated research, pedagogical and organizational activity of scholar, his correspondence, the groups of documents from the personal archives of Il’ko Borschak, Agatangel Kryms’kyi, the collection of maps, etc. The wide spectrum of research interests of Omeljan Pritsak – philology, comparative linguistics, oriental studies, global and Ukrainian history, source studies, bibliography, archaeography, historiosophy, and so on, was relevant for a scholar in gathering his library and determination of its contents. This spectrum also provides a basis for a fuller understanding of the peculiarities of all the periods of the scientific biography of the scholar. The personal library of Omeljan Pritsak tremendously helped him to launch new ideas that he subsequently used in studying the problems of different sciences and contributed fully to the formation the researcher as genuine world-level scholar.